2022
DOI: 10.2147/rmhp.s357567
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Non-Contact Infrared Thermometers for Fever Screening Under COVID-19

Abstract: Purpose Fever is one of the most typical clinical symptoms of coronavirus disease 2019 (COVID-19), and non-contact infrared thermometers (NCITs) are commonly used to screen for fever. However, there is a lack of authoritative data to define a “fever” when an NCIT is used and previous studies have shown that NCIT readings fluctuate widely depending on ambient temperatures and the body surface site screened. The aim of this study was to establish cut-off points for normal temperatures of different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The Hong Kong government’s threshold level for fever is 38 °C for IRTTs and 36.0 °C for NCFITs [ 40 ]. Lai et al and Chen et al suggested temperatures of 36.7 °C [ 41 ] and 36.0 °C [ 38 ], respectively, to screen for fever. Therefore, a well-designed cutoff point validation study is proposed, along with further studies on the influencing factors and limitations of the offset algorithm in the temperature measurement using NCFITs.…”
Section: Discussionmentioning
confidence: 99%
“…The Hong Kong government’s threshold level for fever is 38 °C for IRTTs and 36.0 °C for NCFITs [ 40 ]. Lai et al and Chen et al suggested temperatures of 36.7 °C [ 41 ] and 36.0 °C [ 38 ], respectively, to screen for fever. Therefore, a well-designed cutoff point validation study is proposed, along with further studies on the influencing factors and limitations of the offset algorithm in the temperature measurement using NCFITs.…”
Section: Discussionmentioning
confidence: 99%
“…All investigators have mastered standardized operating procedures of NCITs and MATs (including body surface measurement sites and distance away from surface, ambient temperature measurement and data input) ( 27 ). The fever screening point is located at the entrance of the hospital, and the parking lot is outside the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous preliminary study (27), we have calculated the theoretical optimal diagnostic threshold (the maximal sum of sensitivity and specificity) at each body surface site. For instance, when 37.4 • C at neck was used as fever threshold, the sensitivity of fever screening was 0.866 while the specificity was Abbreviations: CI, confidence interval; NCITs, non-contact infrared thermometers; AUC, area under the curve; MATs, mercury axillary thermometers; ROC, curve receiver operating characteristic curve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices-particularly those that are small and adherent to the patients' body and do not require wired connectionscould be applicable in a wide range of clinical settings, including people with acute neurological diseases. In addition, especially during the COVID-19 pandemic, there was a growing use of forehead temperature measurements in clinical settings as well [23][24][25].…”
Section: Introductionmentioning
confidence: 99%